Implementasi Konsep Manajerial Kurikulum dalam Penguatan Mutu Pembelajaran di Era Transformasi Pendidikan - Ibrahim, Ibrahim; Azis, Khoirul; Musyafa’ah, Rohmatun; Niken, Niken (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the implementation of curriculum managerial concepts in efforts to improve the quality of learning in the era of educational transformation. Rapid digital technological developments and dynamic social changes pose new challenges for the education sector in maintaining the quality and relevance of learning. This research employs a literature review method utilizing secondary data sources, including reference books, reputable national and international journals, scientific proceedings, research reports, and educational policy documents. Data collection was conducted through the stages of inventorying, selecting, and documenting relevant literature. Subsequently, the data were analyzed using content analysis techniques through data reduction, data presentation, and conclusion drawing. The results and discussion indicate that curriculum managerial concepts play a strategic role in ensuring the systematic and effective integration of planning, implementation, and evaluation of learning. However, discrepancies remain between the curriculum, students’ needs, and the continually evolving demands of the labor market. Therefore, strengthening learning quality is an essential requirement through improving teacher competence, implementing effective learning strategies, and increasing students’ active participation. Educational transformation is viewed as a strategic step to align the education system with technological, social, and economic developments